Why do We Need a State? : Justifying Coercion - Fontana Filho, Mauricio (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2020)
This article investigates the motivations for State interventions inside moral, political and economic spheres. If historically the conflicts between State power and individual liberty are generated in abundance, on the other hand, the justifications remain, even in today’s time, as being rationally relevant. Do we really need a State? Is the protection received worth the lost individual liberty? We propose ourselves to investigate such a coercive institution. The main objective is to expose State action and work inside its rationalities. This investigation has as its method the hypothetical-deductive, and makes use of the technic of bibliographical research. Such analysis is of great importance as a means to understand the figure of the State amid the political crisis that surrounds many contemporary countries.